Are you sitting (un)comfortably? Action-based supervision and supervisory drift. (2020) - Pugh, Matthew; Margetts, Alexander
Abstract: Action-based methods such as behavioural experiments, role-play and (by extension) 'chairwork' are powerful techniques recommended in core supervisory texts for cognitive behavioural therapy (CBT). Despite this, experiential methods are seldom used by supervisors, suggesting that supervision often drifts from a 'doing process' to a 'talking process'. A number of factors contribute to this divergence from best practice, including limited confidence and a lack of familiarity with experiential procedures amongst supervisors. To address this, the current paper presents a variety of action-based techniques for enhancing supervisees' technical, perceptual, interpersonal, reflective and personal competencies. Behavioural experiments, empty-chair, multi-chair and role-playing exercises for maintaining treatment fidelity, enhancing empathic attunement, repairing therapeutic ruptures, resolving impasses and working through negative countertransference are described, amongst others. Further research is needed to establish the nature and extent of supervisory drift, as well as the efficacy of action-based methods. Key learning aims: As a result of reading this paper, readers should: (1) Understand why supervision sometimes drifts from being a 'doing' process. (2) Appreciate the value of experiential, action-based supervisory methods. (3) Feel competent using action-based methods to enhance supervisees' clinical skills.